KNOWLEDGE AND PRACTICE OF HYPERTENSION PATIENT ON LIFESTYLE MODIFICATION IN TERTIARY CARE HOSPITAL LAHORE - FATIMA , M; ZAHRA , R; FARWA , U; SARWAR , M; NAWAZ , B (Biological and Clinical Sciences Research Journal, 2024)
Hypertension is a leading cause of cardiovascular morbidity and mortality worldwide. Lifestyle modifications are critical for its management, yet adherence to these changes remains suboptimal, particularly in developing countries like Pakistan. This study aimed to assess the knowledge and practices of hypertensive patients regarding lifestyle modifications in tertiary care hospitals in Lahore. Methods: A descriptive cross-sectional study was conducted among 100 hypertensive patients at Sheikh Zayed Hospital and Social Security Hospital, Lahore. Participants were recruited through convenience sampling, and data were collected using a structured questionnaire covering demographic characteristics, knowledge, and practices. Descriptive and inferential analyses were performed using SPSS version 26. Results: The mean knowledge score was moderate, with 61% of participants aware of lifestyle modifications for hypertension management. Dietary adherence was relatively high, with 67% following a low-salt diet and 78% using healthy cooking oils. However, only 54% engaged in regular physical activity, and 52% discontinued medication once symptoms improved. Knowledge gaps were observed in understanding complications such as cardiovascular and renal diseases. Conclusion: The findings reveal moderate knowledge and fair practices among hypertensive patients, highlighting gaps in understanding complications and adherence to recommended practices. Targeted educational interventions and structured counseling programs are essential to improve patient outcomes and reduce hypertension-related complications.